Total and partial magnetic retained overdenture. A clinical report. - Bogdan-Andreescu Claudia Florina; Bănățeanu Andreea Mariana; Botoacă Oana; Rădulescu Diana Eugenia ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2023)
An overdenture is a denture supported partly by soft tissues and partly by retained teeth or implants. Magnetic tooth-retained overdentures are used to increase support, retention, and stability but also prevent alveolar ridge resorption. Magnetic attachments increase the retention of partial or complete dentures regardless of the path of the insertion and, in addition, can be used for abutment teeth with periodontal disease. This paper discusses two oral rehabilitation cases with total and partial tooth-retained overdenture.